1998
DOI: 10.1046/j.1365-2222.1998.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological characteristics of peanut allergy

Abstract: This study highlights the diversity of peanut allergens. Diagnostic extracts containing a high proportion of the 15 kDa component may aid in diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 30 publications
(60 reference statements)
4
48
0
Order By: Relevance
“…In studies of food allergy there is little data relating clinical severity and IgE level. 19 In study by Clarke et al 20 serum levels of IgE to a 15 kDa protein has been shown to be significantly higher in peanut allergy patients experiencing severe symptoms than those classified as having a moderate or mild reaction. In our study there was no obvious association between the levels of total or specific serum IgE and STAT6 GG genotype in nut allergy patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In studies of food allergy there is little data relating clinical severity and IgE level. 19 In study by Clarke et al 20 serum levels of IgE to a 15 kDa protein has been shown to be significantly higher in peanut allergy patients experiencing severe symptoms than those classified as having a moderate or mild reaction. In our study there was no obvious association between the levels of total or specific serum IgE and STAT6 GG genotype in nut allergy patients.…”
Section: Discussionmentioning
confidence: 98%
“…These include the major storage proteins arachin and conarachin, peanut lectin and phospholipase D, the acidic glycoprotein, peanut 1 and three major allergens, which have been characterised and sequenced as Ara h1, 2 and 3. 20 Current in vitro tests cannot distinguish between patients experiencing mild or severe nut allergic reactions, or predict the likely event of a likely further severe reaction. Given that the STAT6 homozygous GG genotype is associated with a more severe phenotype it may be possible that such information, when combined with other genetic and laboratory data, could help predict the risk of subsequent severe reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although about 11 peanut allergens have been reported (www.allergome.org), Ara h 1, Ara h 2, and Ara h 3 are classified as the major peanut allergens because they are generally recognized by more than 50% of peanut-allergic patients (Koppelman et al, 2001). Specifically, Ara h 1 and Ara h 2 are recognized by 70% to 90% of patients with peanut allergy (Burks et al, 1995bClarke et al, 1998), and Ara h 3 is recognized by serum IgE from approximately 44% to 54% of different patient populations with a history of peanut sensitivity (Kleber-Janke et al, 1999;Rabjohn et al, 1999).…”
mentioning
confidence: 99%
“…Thus, it is critical for African countries to develop local low cost screening tests and kits, for food and peanut allergies. Among the large array of panels available, serological tests to identify specific IgE antibodies to peanut may be an appropriate screening strategy to be developed large scale as suggested by some authors [19,20] .Enzyme immunoassays are used to determine not only peanut proteins but traces of allergens in food and feeds [21,19,22] . The main objective of this study was to identify the protein profile of peanut seeds from Côte d'Ivoire and compared the molecular specificities of the major allergens to that of Georgia green peanut seeds from the USA using a combination of SDS PAGE and western blots.…”
mentioning
confidence: 99%